Konsep Bimbingan Konseling Berfokus Solusi Dalam Islam - Miftahul Huda; Erny Fitroh Nabila Muwafiqi; Slamet Slamet (Universitas 45 Surabaya, 2023)
The purpose of this research is to describe the development of BK and Counseling Solution Focused Brief Therapy (SFBT) into Islamic-based SFBT guidance and counseling theory and practice. The type of research used in this research is library research on literature review objects by exploring data sources from books and digital or manual journals related to the theory and practice of Islamic-based SFBT guidance and counseling. The result of this research is the development of guidance and counseling services using the Solution Focused Brief Therapy (SFBT) approach to becoming guidance and counseling services with an Islamic-based SFBT approach and the practice of Islamic-based guidance and counseling services. The practice of Islamic-based SFBT guidance and counseling can be divided into four stages, namely: pre-session therapy, guidance, intervention, and closing of the session.